2011
DOI: 10.1084/jem.20111155
|View full text |Cite
|
Sign up to set email alerts
|

Immature B cells preferentially switch to IgE with increased direct Sμ to Sε recombination

Abstract: To be added.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 66 publications
(103 reference statements)
3
79
2
2
Order By: Relevance
“…Although IgE is a class-switched Ig-isotype requiring CD40L expression by T helper cells [20], total IgE levels are relatively high in mice or humans with T helper cell defects or complex human immunodeficiencies such as Wiskott Aldrich or Omenn syndrome [7,21]. Class-switching to IgE can happen either directly or in a stepwise fashion via classswitching first to IgG1 and then to IgE [22]. Immature B cells switch preferentially from IgM directly to IgE by passing the intermediate class switch to IgG1 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although IgE is a class-switched Ig-isotype requiring CD40L expression by T helper cells [20], total IgE levels are relatively high in mice or humans with T helper cell defects or complex human immunodeficiencies such as Wiskott Aldrich or Omenn syndrome [7,21]. Class-switching to IgE can happen either directly or in a stepwise fashion via classswitching first to IgG1 and then to IgE [22]. Immature B cells switch preferentially from IgM directly to IgE by passing the intermediate class switch to IgG1 [22].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the increase in IL-27 production was crucial for the development of T FH cells and T-cell help to B cells for the production of IgG and survival, which might contribute to development of long-term humoural responses to, for example, parasites such as S. mansoni and F. hepatica that express various fucose-based glycan PAMPs 26 . [4][5][6]8 . Thus, our results suggest that DC-SIGNmediated DC priming via IKKe can provide the signals for establishing long-term humoural immunity via induction of both T FH and T H 2.…”
Section: Discussionmentioning
confidence: 99%
“…T FH cells produce interleukin (IL)-21, a potent cytokine that drives antibody isotype class switch recombination and B-cell proliferation, together with other factors 2,3 . Once B cells are outside GCs, IL-4 produced by T H 2 cells induces isotype switching to immunoglobulin E (IgE) antibodies [4][5][6] , which are integral in eosinophil-mediated killing and expulsion of parasitic worms from the intestines 1,7 . Sequential switching of IgG cells to IgE is essential for the development of long-lived high-affinity IgE þ plasma cells 8 .…”
mentioning
confidence: 99%
“…Outlined here is a strategy that has been utilized to conduct CSR assays and detect true IgE-expressing B cells from mice [9][10][11] . Treatment of activated B cells with trypsin, a common lab reagent to digest protein, removes both cytophylic and membrane bound surface IgE.…”
mentioning
confidence: 99%
“…B cells can be activated for CSR in the context of total splenocytes 12 or as purified splenic B cells 11 . As noted in the protocol (step 2.3), B cell enrichment is optional, and is at the discretion of the experimenter to determine if it would beneficial.…”
mentioning
confidence: 99%